Amplification of the discharge current density of lithium-ion batterieswith spinel phase Li(PtAu)0.02Mn1.98O4nano-materials - Mailu, Stephen N.; Iwuoha, Emmanuel I.; Ikpo, Chinwe O.; Baker, Priscilla; Njomo, Njagi; Masikini, Milua; Matinise, Nolubabalo; Tsegaye, Abebaw; Mayedwa, Noluthando; Waryo, Tesfaye; Ozoemenab, Kenneth I.; Williams, Avril (Elsevier, 2014)
In this study the synergistic and catalytic properties of a novel nano-composite cathode material ofnominal composition Li(M)xMn2-xO4(M = Pt-Au; x # 0.2) has been explored. Li(PtAu)xMn2-xO4nano-material for use in lithium-ion batteries (LIB) was synthesized by incorporation of the Pt-Au (1:1)nanoparticles onto the spinel phase LiMn2O4.Ultra-low scan rate (0.01 mV s−1) cyclic voltammetryof the cathode material in 1 M LiPF6(in 1:1 EC:DMC), showed four sets of redox peaks, which reflectthe typical redox process of the active material in the spinel structure due to lithium intercalation anddeintercalation. The Li/Li(PtAu)0.02Mn1.98O4cell had less polarization as it effectively accommodates thestructural transformation during Li+ion charge and discharge. The Li(PtAu)0.02Mn1.98O4cathode showedan increase in discharge currents densities with an exchange current density, i0, value of 2.8 × 10−4Acm−2, which suggests increase in the rate of electron transfer compared to LiMn2O4(1.8 × 10−4A cm2).Li(PtAu)0.02Mn1.98O4exhibited excellent capacity retention upon extended cycling and can release 90mAh g−1at 10C with a capacity retention of 99% after 50 cycles. Faster charge transportation at high cur-rent rates proved to prevent the pronounced pile-up of Li+ions and undesired Mn3+ions on the surfaces.The electrochemical impedance spectroscopy (EIS) results showed a decrease in charge transfer resis-tance for LiMn2O4after surface coverage with conductive PtAu NP’s. For the lithium diffusion coefficientin Li(PtAu)0.02Mn1.98O4thin film, its magnitude order is 10−11cm2·s−1.
Copyright: 2015 Elsevier. Due to copyright restrictions, the attached PDF only contains the abstract of the full text item. For access to the full text item, please contact the publisher's website. The definitive version of the work is published in Electrochimica Acta, vol. 128, pp 178-183
Keywords: Lithium-ion batteries